SUSTAINABLE WASTE MANAGEMENT IN CONSTRUCTION: CHALLENGES AND STRATEGIES (REMUNOM, 2024)
This study addresses the topic of waste management in civil construction, highlighting its importance for sustainability and minimizing environmental impacts. The main objective is to analyze the current state of waste management practices in Brazil, identifying the main barriers and proposing sustainable improvements. To achieve this goal, a comprehensive literature review was conducted, exploring the classification and types of waste in civil construction, successful waste management practices, and specific challenges in the Brazilian context. The methodology included the analysis of data and information from reliable sources such as Scielo databases, Google Scholar, and civil engineering journals. The results revealed that, although there are significant advances in some areas, such as the implementation of waste management technologies, there are still important challenges to be overcome. Lack of awareness, scarcity of adequate infrastructure, and the need for greater commitment from stakeholders were identified as the main obstacles. The main conclusion of this work is that waste management in civil construction requires an integrated approach, involving public policies, responsible business practices, and societal engagement. It is essential to promote awareness, training, and investment in sustainable technologies to achieve efficient and environmentally responsible management.